(x+3)平方-(x-1)(x-2)=
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 23:08:56
(x+3)平方-(x-1)(x-2)=(x+3)平方-(x-1)(x-2)=(x+3)平方-(x-1)(x-2)=x平方+6x+9-(x平方-3x+2)=x平方+6x+9-x平方+3x-2=9x+7
(x+3)平方-(x-1)(x-2)=
(x+3)平方-(x-1)(x-2)=
(x+3)平方-(x-1)(x-2)=
x平方+6x+9-(x平方-3x+2)=x平方+6x+9-x平方+3x-2=9x+7
方程2/X平方+X+3/X平方-X=4/X平方-1
x平方-3[2x-5(x平方-x+1)]
(x平方+x)(x平方+x-2)=-1 用换元法
若x平方+x-1=0,则2x立方-3x平方-x=?
-5x(-x的平方+2x+1)-(2x+3)(5-x的平方)=
3X平方+X-5-2(4-X+7x平方)其中x=-1
6x+2x的平方-3x+x的平方+1,其中x=5
x/x平方-x+2=2x/x+1
(2x平方-3x+1)平方=22x平方-33x +1解方程
X平方+3x+1=0 求:2x平方+X平方 分之 2
(x+1)(x-1)+2x(x+2)=3(x的平方+1),求X.
解方程(x平方+x-3)/(x平方+x-2)+1=(2x平方+4x+1)/(x平方+2x+1)
5x平方-[x平方 (5x平方-2x)-(2x平方-3x)]其中x=-2分之一
(1-x/3-x)平方除以x平方-6x+9/9-x平方*1/x平方-2x+1
(x平方-1)的平方-(2x+2)平方 (x平方+x)(x平方+x-2)-3(x平方-1)的平方-(2x+2)平方(x平方+x)(x平方+x-2)-3分解因式
X(x平方-6x-9)-x(x平方-8x-15)+2x(3-x)其中x=-六分之一
根号3(x平方-1)=x(x-2)+1
(x+3)平方-(x-1)(x-2)=